Methane dry reforming over Ce-promoted Ni/Al2O3 catalyst : kinetic studies - Muhamad Hisyam, Zakaria (2015)
Syngas (or H2 and CO mixture) production has received significant attention since it is the main feedstock of Fischer-Tropsch synthesis for synthetic fuel manufacture to replace petroleum-based energy. Dry reforming of methane (DRM) has been considered as an efficient and green approach for producing syngas due to greenhouse gas utilization and desired syngas composition. In this research, the objectives were to prepare 3%Ce-10%Ni/Al2O3, to investigate the physicochemical attributes of 3%Ce-10%Ni/Al2O3 catalyst and examine the effect of reactant partial pressure on DRM performance. XRD diffractograms indicated the formation of CeO2, NiO and NiAl2O4 phases corroborated with temperature-programmed calcination (TPC) results. The complete thermal decomposition and oxidation of metal precursors were observed at 750 K during TPC measurement. DRM performance over 3%Ce-10%Ni/Al2O3 catalyst was stable with time-on-stream for all CO2:CH4 ratios. CH4 and CO2 reaction rates enhanced with growing CO2 partial pressure (PCO2) and exhibited a maximum at PCO2=30 kPa. CH4 conversion enhanced with growing CO2 partial pressure (PCO2) and exhibited a maximum at PCO2=40 kPa and CO2 conversion vice versa to the CH4 conversion. H2 , CO selectivity and yield enhanced with lessen CO2 partial pressure (PCO2) and exhibited a maximum at PCO2=20 kPa. Interestingly, H2/CO ratio also reduced with an increase in CO2 partial pressure and the ratio of H2/CO was always inferior to unity for all runs reasonably due to the reverse water-gas shift reaction.